Physicochemical properties of CO2-cured belite-rich cement with electric arc furnace reduction slag as a partial replacement - Geon Noh; Gaurav Sharma; Hyeju Kim; Kunal Krishna Das; Jeong Gook Jang; Jung-Jun Park; Namkon Lee (Developments in the Built Environment)
This study investigates the physicochemical properties of CO2-cured belite-rich cement with electric arc furnace (EAF) reduction slag as a partial replacement at varying weight percentages (0–20%). The results revealed that water-cured specimens (WRS) showed significant increases in the numbers of gel and medium capillary pores, while carbonation-cured specimens (CRS) demonstrated increases in the numbers of large capillary and macro pores. Moreover, up to 10% replacement of the slag led to a decrease in the compressive strength, accompanied by increased CO2 absorption and reduced alkalinity. When the EAF reduction slag content increased from 15% to 20%, CRS exhibited a trend reversal in the compressive strength, marked by an increase in the pH, approaching compressive strength comparable to those of WRS. This signified that higher percentages of EAF reduction slag are advantageous for enhancing CO2 sequestration due to the potential reactivity of magnesium oxide in EAF reduction slag with CO2.